Rural outmigration and the gendered patterns of agricultural labor in Nepal - Slavchevska, Vanya; Doss, Cheryl R.; Mane, Erdgin; Kaaria, Susan; Kar, Anuja; Villa, Victor (International Food Policy Research Institute, 2020)
In Nepal, as in many developing countries, male outmigration from rural areas is significant and is rapidly transforming the sending communities. Using primary data collected from households in rural Nepali communities, this study analyzes the effects of male out-migration from rural agricultural areas on women’s and men’s work on and off the farm. Using an instrumental variable approach to correct for endogeneity related to outmigration, the study finds differential impacts on agricultural labor for the men and women who remain. Men reduce labor in non-farm work without significantly increasing their labor allocation to other activities. Women, on the other hand, increase their work on the farm taking on new responsibilities and moving from contributing family workers to primary farmers. Despite their growing roles as primary farmers, women in households with a migrant do not increase their work in higher value activities, and remain predominantly concentrated in producing staple grains. The analysis highlights the importance of recognizing the changing roles of rural women, especially with respect to the management of the family farm, but it also raises questions about the sustainability and resilience of rural livelihoods to shocks in remittance incomes.